Penggunaan Benda Asli pada Ceramah untuk Meningkatkan Pengetahuan, Sikap dan Kondisi Lingkungan, di SDN Klodangan dan SDN Berbah I, Sleman - Dewi Arfiyanti; Lucky Herawati; Lilik Hendrarini (Poltekkes Kemenkes Yogyakarta, 2016)
Keeping the cleanliness of toilet and proper waste disposal are examples of clean and healthy live behaviors. Behavior has three domains, namely: knowledge, attitude, and practice. The study was aimed to know the influence of employing real object in elucidation toward elementary school students’ knowledge and attitude, as well as the environment condition of their schools which were related with proper waste disposal and toilet cleanliness. A quasi experiment with non-equivalent pre-post control group design was conducted. Differ from the control group, In the treatment group, the elucidation was accompanied by the use of real objects. As the studysubject were all 5th grade students of Berbah I Elementary School as the control group (30 students) and of Klodangan Elementary Schools as the treatment group (34 students). The data were analyzed by using non-parametric Mann-Whitney test at 5 % significance level because the data were not normally distributed. Since the all p-values indicated below 0,05, the result shows that elucidation with real objects influencing the changes in knowledge and attitude among the students, as well as the environment condition in the study sites.